Strategi Manajemen Kurikulum Untuk Meningkatkan Mutu Pendidikan di SMP Negeri 5 Medan - Jayu Alkautsar Rabbani (-, 2021)
The purpose of this study was to find out how the problems and strategiesimplemented by curriculum management to improve the quality of education atSMP Negeri 5 Medan. The method used in this study is a qualitative descriptivemethod. The instruments used in this study were observations observed by theresearchers themselves and through interviews with one of the Islamic ReligiousEducation teachers at SMP Negeri 5 Medan. The research results obtained are:The problems of curriculum management at SMP Negeri 5 Medan are about: 1)Lack of variety of learning methods applied in the learning process. 2)There is no implementation of remedial activities in evaluating the abilities of students. 3)Students lack insight into technology. Strategies that must be carried out to improve the education system at SMP Negeri 5 Medan, including: 1) There is a need for curriculum development, 2) There is a need for funding for books in the library, 3) Completing teaching aids such as practical training equipment facilities to facilitate the learning process , 4) Arrangement of teachers is carried out.